Methylprednisolone pulse versus docetaxel in recurrent thymoma with myasthenia gravis - Yang, Hongxia; Wang, Yaxuan; Pan, Zulin; Liu, Ze; Cheng, Biqi; Qi, Guoyan (Frontiers in Neurology, 2025)
IntroductionThis study aims to compare the effectiveness and safety of methylprednisolone pulse versus docetaxel in treating recurrent thymoma with myasthenia gravis (MG).MethodsWe conducted a single-center, open-label, retrospective study that included 90 patients with thymoma recurrence accompanied by MG, who were treated with either methylprednisolone pulse or docetaxel. Compared the improvement rate of the Myasthenia Gravis Foundation of America Post-intervention Status (MGFA-PIS) and Quantitative Myasthenia Gravis Score (QMGS), changes in acetylcholine receptor antibodies (AchR-AB), and alterations in thymoma after treatment. Adverse events were also recorded.ResultsBoth treatments significantly reduced QMGS and AchR-AB levels (p < 0.05). For MG, the overall effective rate (ORR1) was similar between groups (p > 0.05). However, the methylprednisolone group showed a higher objective response rate (ORR2) and disease control rate (DCR) for thymoma (p < 0.05). The incidence of adverse reaction incidence was 66.7% for the methylprednisolone group and 44.4% for the docetaxel group (p < 0.05).DiscussionMethylprednisolone is more effective against thymoma than docetaxel for recurrent thymoma with MG, but has greater side effects. Docetaxel has similar MG efficacy compared to methylprednisolone, and with fewer side effects. The choice of treatment should be based on the patient’s specific clinical situation.